Seedling nutrient status before submergence affects survival after submergence in rice - Ella, Evangelina S.; Ismail, Abdelbagi M. (Wiley, 2006)
Vast rainfed lowland areas in Asia periodically experience flash floods that adversely affect survival and productivity of rice (Oryza sativa L.). Progress has been made in developing more tolerant germplasm, but fewer efforts have been devoted to identifying proper management options. We evaluated the effects of nitrogen (N) and phosphorus (P) added before submergence on seedling survival after submergence. Two experiments were conducted using two cultivars, submergence‐tolerant FR13A and intolerant IR42. In the first experiment, N was applied at two different times and, in the second, N and P were used in a fertile and a P‐deficient soil. Seedlings (21‐d‐old) were submerged in concrete tanks for 12 d. Addition of P seems to enhance tolerance of plants grown on P‐deficient soils. Survival of both cultivars decreased substantially in seedlings with high N concentration, with higher survival in FR13A. Leaf N and chlorophyll concentration before submergence were higher in N‐treated seedlings, whereas chlorophyll a/b ratio was lower. In both cultivars, photosynthesis and root–shoot ratio decreased and chlorophyllase activity increased after submergence with increasing N and with higher activity of chlorophyllase in IR42. Survival was negatively correlated with leaf N concentration, but positively correlated with root–shoot ratio and stem starch concentration before submergence and with chlorophyll concentration and chlorophyll a/b ratio after submergence. Crop establishment could therefore be enhanced in areas where untimely flooding is anticipated by avoiding excessive N application.